Pengaruh Beban Kerja, Stres Kerja dan Motivasi Terhadap Kinerja Pegawai di Dinas Perhubungan Kabupaten Probolinggo - Habiba Miftahul Ilmi; Hermanto Hermanto; Dyah Ayu Perwitasari (JUMAD : Journal Management, Accounting, & Digital Business, 2023)
The research was conducted on the Probolinggo Regency Transportation Office with the aim of knowing the effect of workload, work stress and motivation on employee performance at the Probolinggo Regency Transportation Service. The type of research used is quantitative with an associative approach. The population in this study used was all civil servants as many as 67 people. Sampling using saturated sampling technique. The sample in this study were all civil servants as many as 67 people. The data sources used in this study come from primary data and secondary data. Data were collected through questionnaires and completed through data analysis methods in the form of validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, coefficient of determination and hypothesis testing. The results of the study show that workload has a positive and significant effect on employee performance, work stress has a positive and significant effect on employee performance and motivation has a positive and significant effect on employee performance.